Analisis Kinerja Dokter Verifikator Internal dalam Menurunkan Angka Klaim Pending di RSUD Koja Tahun 2018 - Kusumawati, Ayu Nadya; Pujianto, Pujianto (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
The doctor's internal verifier has an important task in reducing the number of pending claims especially for controlling the suitability of coding with diagnoses on medical resumes. This research explain that the performance of internal verifier doctors in reducing the number of pending claims in Koja Hospital in 2018 by reviewing claims files and observations on claim data from 2017 to 2019. This study uses an intervention evaluation study design by analyzing quantitative and qualitative data. The method used is to compare data coding errors on pending hospitalization claims Pre-intervention and Post-Intervention doctor internal verifiers both in number of claims and nominal claims. Then conduct in-depth interviews to find out the cause of coding errors to cause pending claims. The results of this study are that the proven internal verifier can reduce the number of pending hospitalization claims due to coding errors and obtained the causes of coding errors, namely incomplete medical resumes, lack of coder accuracy, lack of coder knowledge, lack of uniformity of information related to claim file coding and overload not accompanied by suitability of the number of coders. This can be minimized by the use of electronic medical records, training of coder personnel, team building and the addition of coder personnel.